Tenascin and aggrecan expression by articular chondrocytes is influenced by interleukin 1β: a possible explanation for the changes in matrix synthesis during osteoarthritis. Issue 3 (12th February 2004) - Pfander, D; Heinz, N; Rothe, P; Carl, H-D; Swoboda, B
Abstract : Objective: To analyse the distribution patterns of tenascin and proteoglycans in normal and osteoarthritic cartilage, and to determine the effect of interleukin 1β (IL1β) on aggrecan and tenascin expression by human articular chondrocytes in vitro. Methods: Normal and osteoarthritic cartilage and bone samples were obtained during total knee replacements or necropsies. After fixation and decalcification, paraffin embedded specimens were sectioned perpendicular to the surface. Specimens were graded according to Mankin and subdivided into those with normal, and mild, moderate, and severe osteoarthritic lesions. Serial sections were immunostained for tenascin. Tenascin expression by healthy and osteoarthritic chondrocytes was quantified by real time polymerase chain reaction (PCR). Furthermore, in cell culture experiments, human articular chondrocytes were treated with 0.1 or 10 ng/ml IL1β. Real time PCR analyses of aggrecan and tenascin transcripts (normalised 18S rRNA) were conducted to determine the effect of IL1β on later mRNA levels. Results: Tenascin was immunodetected in normal and osteoarthritic cartilage. In osteoarthritic cartilage increased tenascin staining was found. Tenascin was found specifically in upper OA cartilage showing a strong reduction of proteoglycans. Greatly increased tenascin transcript levels were detected in osteoarthritic cartilage compared with healthy articular cartilage. IL1β treatment of articular chondrocytes in vitro significantly increased tenascin transcripts (~200% of control) and strongly reduced aggrecan mRNA levels (~42% of control). Conclusions: During progression of osteoarthritis the switch in matrix synthesis occurs mainly in upper osteoarthritic cartilage. Furthermore, changes in synthesis patterns of osteoarthritic chondrocytes may be significantly influenced by IL1β, probably diffusing from the joint cavity within the upper osteoarthritic cartilage.